Characterization of transmissible gastroenteritis coronavirus S protein expression products in avirulent S. typhimurium Δcya Δcrp: persistence, stability and immune response in swine - Smerdou, Cristian (Vet Microbiol, 1996)
The spike protein from transmissible gastroenteritis virus (TGEV) was expressed in attenuated S. typhimurium Δcya Δcrp Δasd χ3987. Three partially overlapping fragments of TGEV S gene, encoding the amino-terminal, intermediate, and carboxy-terminal end of the protein, as well as the full length gene were inserted into the asd(+) plasmid pYA292 to generate recombinant plasmids pYATS-1, pYATS-2, pYATS-3, and pYATS-4, respectively, which were transformed into S. typhimurium χ3987. Recombinant S. typhimurium χ3987 (pYATS-1) and χ3987 (pYATS-4) expressing constitutively a 53 kDa amino-terminal fragment of the S protein and the full length protein (144 kDa), respectively, showed high stability. After 50 generations in vitro 60% and 20% of the bacteria transformed with pYATS-1 and pYATS-4, respectively, expressed the S-protein antigen. Since S. typhimurium χ3987 (pYATS-1) showed a better level of expression and stability in vitro, this recombinant strain was selected as a potential bivalent vector to induce both immunity to Salmonella and TGEV in swine. In order to study colonization of swine tissues by S. typhimurium Δcya Δcrp, a gene conferring resistance to rifampicin was cloned into the chromosome of S. typhimurium χ3987, generating χ4509 strain. Both S. typhimurium χ4509 (pYA292) and χ4509 (pYATS-1) colonized the ileum of orally inoculated swine with clearance of bacteria between days 10–20 post-infection. The expression of the amino-terminal fragment of the S protein diminished the ability of S. typhimurium χ4509 (pYATS-1) to colonize deep tissues. The recombinant strain S. typhimurium χ3987 (pYATS-1) induced TGEV specific antibodies in both serum and saliva of orally inoculated swine. This strain, as well as S. typhimurium χ3987 (pYA292), also elicited both systemic and mucosal immunity to Salmonella antigens.